2008
DOI: 10.1111/j.1399-3046.2007.00875.x
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of Norwalk virus enteritis following small bowel transplantation treated with oral human serum immunoglobulin

Abstract: Protracted diarrhea is a challenging problem after small bowel transplantation. We report two patients who developed Norwalk virus enteritis after small bowel transplantation. Both received oral HSIG with resolution of diarrhea within 48 h.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 13 publications
2
45
0
Order By: Relevance
“…Several strategies have been tried in limited numbers of patients: oral or intravenous immunoglobulin, breast milk, ribavirin, and nitazoxanide. Several case series have suggested that oral human immunoglobulin improves diarrheal symptoms; however, a recent cohort study failed to demonstrate improvements in total time to resolution of diarrhea, length of hospital stay, or cost with administration of oral human immunoglobulin [40,53,62,63]. Systemic administration of immunoglobulin has also provided conflicting evidence on clinical impact [40].…”
Section: Norovirusmentioning
confidence: 94%
“…Several strategies have been tried in limited numbers of patients: oral or intravenous immunoglobulin, breast milk, ribavirin, and nitazoxanide. Several case series have suggested that oral human immunoglobulin improves diarrheal symptoms; however, a recent cohort study failed to demonstrate improvements in total time to resolution of diarrhea, length of hospital stay, or cost with administration of oral human immunoglobulin [40,53,62,63]. Systemic administration of immunoglobulin has also provided conflicting evidence on clinical impact [40].…”
Section: Norovirusmentioning
confidence: 94%
“…Siebenga et al [10] reported prolonged illness and viral shedding (21-182 days) in hospitalized patients. Chronic norovirus infection has been reported in pediatric intestinal transplant recipients and in a child with cartilage hair hypoplasia after bone marrow transplantation [11][12][13]. Ludwig et al [14] found a prolonged shedding over a maximum of 433 days in pediatric patients with cancer.…”
mentioning
confidence: 97%
“…Unfortunately, there are no approved therapeutics or vaccines for controlling norovirus infections. Attempted methods to control chronic infection have included treatment with drugs effective against other diarrheal diseases (27), adjustment of the immunosuppressive drug type or dosage (28), and oral or enteral administration of human IgG (29)(30)(31)(32). Although reduction in immunosuppression coupled with IgG administration has shown promise for some transplant patients, IgG therapy has failed in other studies, and reduction of immunosuppression is not always possible.…”
mentioning
confidence: 99%